Ultrabroadband absorptive refractory plasmonics for photocatalytic hydrogen evolution reactions - Myeongcheol Go; Inju Hong; Dasol Lee; Sanghoon Kim; Junho Jang; Keon-Woo Kim; Sangmin Shim; Kijung Yong; Junsuk Rho; Jin Kon Kim (NPG Asia Materials)
Abstract As an environmentally friendly and renewable method for hydrogen production powered by solar energy, photocatalytic hydrogen evolution reactions (HERs) using broadband absorbers have received much attention. Here, we report the fabrication and characterization of an ultrabroadband absorber for the photocatalytic HER. The absorber is composed of titanium nitride and titanium dioxide heterostructures deposited onto a porous anodized aluminum oxide template. The absorber shows ultrabroadband absorption in both the visible and near-infrared regions (400–2500 nm), with averages of 99.1% and 80.1%, respectively. Additionally, the presence of the TiO2 layer within the absorber extends the lifetime of the hot carriers by 2.7 times longer than that without the TiO2 layer, enhancing the transfer of hot electrons and improving the efficiency of hydrogen production by 1.9 times. This novel ultrabroadband absorber has potential use in advanced photocatalytic HER applications, providing a sustainable and cost-effective route for hydrogen generation from solar energy.